Lipidbook: a public repository for force-field parameters used in membrane simulations. - Domański, J; Stansfeld, P; Sansom, MS; Beckstein, O (2010)
Lipidbook is a public database for force-field parameters with a special emphasis on lipids, detergents and similar molecules that are of interest when simulating biological membrane systems. It stores parameter files that are supplied by the community. Topologies, parameters and lipid or whole bilayer structures can be deposited in any format for any simulation code, preferably under a license that promotes "open knowledge." A number of mechanisms are implemented to aid a user in judging the appropriateness of a given parameter set for a project. For instance, parameter sets are versioned, linked to the primary citation via PubMed identifier and digital object identifier (DOI), and users can publicly comment on deposited parameters. Licensing and, hence, the conditions for use and dissemination of academically generated data are often unclear. In those cases it is also possible to provide a link instead of uploading a file. A snapshot of the linked file is then archived using the WebCite(®) service without further involvement of the user or Lipidbook, thus ensuring a transparent and permanent history of the parameter set. Lipidbook can be accessed freely online at http://lipidbook.bioch.ox.ac.uk. Deposition of data requires online registration.